Green bridge crops to manage corn nitrogen nutrition in the Southeastern Argentinean Pampas - Crespo, Cecilia; Corral, Raúl Alejandro; Diez, Santiago; Delgado, Santiago Germán; Dominguez, Germán; Agostini, Maria De Los Angeles; Cendoya, María Gabriela; Sainz Rozas, Hernan Rene; Garcia, Gisela Vanesa; Studdert, Guillermo (Elsevier, 2022)
An ecological intensification of agriculture through the use of green bridge crops (GBC) between cash crops is a way to improve resource use efficiency. This study aimed to assess vetch (Vicia villosa Roth.) (Ve), oat (Avena sativa L.) (Oa), Oa+Ve as GBC, and a control without GBC, with different termination dates (early and late), tillage systems (conventional tillage and no-tillage), and nitrogen (N)-fertilization to corn (Zea mays L.) (NF: 0 and 120 kg N ha−1) on soil N availability, and corn N uptake and yield. Three field experiments were carried out at the Southeastern Argentinean Pampas in 2012–2013, 2013–2014, and 2014–2015 on an Argiudoll. Corn and GBC aboveground dry matter and N accumulation and corn grain yield were determined. Soil nitrate-N at corn planting and V6 and anaerobically mineralizable N (AN) at corn planting were also determined. Water availability at corn planting was not limiting, whereas along corn cycle differed among years. The GBC terminated late accumulated more dry matter and N than those terminated early and Ve and Oa+Ve more N than Oa. Both early termination date and Ve tended to show higher nitrate-N at planting and at V6 stage. In general, NF improved corn behavior but response was different among GBC, being lower after Ve and Oa+Ve, and with late termination date. A simple model was fitted to predict corn relative yield based on nitrate-N at V6 stage, AN, GBC dry matter accumulation and C:N ratio. The model fitted allowed predicting relative corn grain yield and could be used as a tool to help N fertilization recommendation.